Effect of Herbal Mouthwash on Salivary pH in Orthodontic Patients - Israa R. Alkasso; Ghada A. Taqa; Sarmad S. Al qassar (University of Mosul, College of Dentistry, 2020)
Aims: The aims of present study were to analyze herbal mouthwash effects on salivary buffering capacity of orthodontic patients after acidogenic challenge by taking a carbonated beverage (coca cola® soft drink), in comparison with baseline pH and determine the duration of action of this mouthwash at which it will persist to protect teeth enamel and oral mucosa from acidic pH. Materials and Methods: Ten patients wearing fixed orthodontic appliances were included in this study. baseline pH for each patient was detected. Each patient was instructed to take one cup of carbonated beverage (coca cola), the mouth pH was re measured directly after coca cola drinking. The patients were asked to gargle with herbal mouthwash for 5-10 seconds, the saliva pH was re detected for each patient after 0, 5,10,15 minute. Results: A significant reduction in salivary pH was found after coca cola drinking (5.47 ± 0.689) was found in comparison with baseline pH (6.65 ± 0.303), salivary pH at 0, 5, 10 and 15 mins from herbal Mouthwash (6.79 ± 0.110), (6.7 ± 0.115) , (6.58 ± 0.139) and (6.53 ± 0.188) respectively at (P value<0.05), while there were no differences among rest pH measurements. Conclusion: application of herbal mouthwash elevated saliva pH directly higher than baseline pH and was effective in enhancing saliva buffering capacity. However, there were no significant differences in pH after taking herbal mouthwash at different times.